Perencanaan dan Perancangan Produk Wastafel dan Fitur Sabun Otomatis Dengan Metode Nigel Cross - Muhammad Anton Alifandi; Ferida Yuamita (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
We are encouraged to wash our hands for 20 seconds, if there is no soap and running water, we can replace it with a hand sanitizer with a minimum alcohol content of 60%. By washing our hands, we can prevent viral infections in ourselves, those around us and even communities such as families and workplaces. Manual hand washing facilities or equipment that are used together can be a medium for spreading viruses so they must be minimized, one of which is by using an Automatic Sink. Because of this, automatic sink products were built to make it easier for users to wash their hands while reducing contact with water taps and soap or bar soap containers. This automatic sink was designed using the Nigel Cross method so that it can realize an automatic handwashing device with the addition of an automatic soap feature that can help the hand washing process without touching the water faucet and soap. The advantage of this method is that it covers all aspects of the design process starting from clarifying the problem to the details of the design. The new product attributes that are arranged by designers are adjusted to the needs of the community, starting from materials to product functions. Based on testing several tasks and answers from the questionnaire answered by respondents, namely as many as 30 respondents to this sink product, it can be said that the attributes used are valid data. The results of the validity test were then carried out by a reliability test with the aim of testing the level of consistency of data measurement. The results of this reliability test produce a Crounchbach's Alpha value of 0.709, which means it is reliable because it is > 0.6.